Protecting Human rights within Regional Economic Integration arrangements: A case study of the SADC tribunal - Simbyakula, Sambwa (Department of Public Law, 2014)
Colonialism left many African states both politically and economically fragile as a consequence of the partitioning of Africa by colonialists. The African states experienced difficulty surviving against Western economies so in response to this legacy, the new African leaders at independence called for political and economic integration. A huge ideological divide ensued in the early 1960s because not every nationalist was enthusiastic about political and economic integration. Therefore, at the continental level, a weak political integration process began with the Organisation of African Unity (OAU) being formed in 1963.